2014
DOI: 10.1007/s12035-014-8659-z
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Enhancement of Brain-Derived Neurotrophic Factor Signaling Pathway Improves Cognitive Impairments Induced by Isoflurane Exposure in Aged Rats

Abstract: Isoflurane-induced cognitive impairments are well documented in animal models; yet, the molecular mechanisms remain largely to be determined. In the present study, 22-month-old male Sprague-Dawley rats received 2 h of 1.5 % isoflurane or 100 % oxygen daily for 3 consecutive days. For the intervention study, the rats were intraperitoneally injected with 1.2 g/kg sodium butyrate 2 h before isoflurane exposure. Our data showed that repeated isoflurane exposure significantly decreased the freezing time to context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 33 publications
2
49
0
Order By: Relevance
“…The BDNF‐TrkB signalling pathway is one of the downstream regulating targets of histone acetylation, so BDNF‐TrkB signalling pathway may be one of the underlying downstream mechanisms of learning and memory deficits induced by propofol exposure during early gestation. It is confirmed that HDAC2 up‐regulation will impair BDNF‐TrkB signalling pathway and results in cognitive impairments induced by isoflurane 54. Our previous study also verified the role of BDNF‐TrkB signalling pathway in the cognitive deficits induced by propofol during late pregnant stage 5.…”
Section: Discussionsupporting
confidence: 79%
“…The BDNF‐TrkB signalling pathway is one of the downstream regulating targets of histone acetylation, so BDNF‐TrkB signalling pathway may be one of the underlying downstream mechanisms of learning and memory deficits induced by propofol exposure during early gestation. It is confirmed that HDAC2 up‐regulation will impair BDNF‐TrkB signalling pathway and results in cognitive impairments induced by isoflurane 54. Our previous study also verified the role of BDNF‐TrkB signalling pathway in the cognitive deficits induced by propofol during late pregnant stage 5.…”
Section: Discussionsupporting
confidence: 79%
“…All behavioral procedures were conducted at daytime from 2:00 PM to 5:00 PM in a sound-isolated room. All behavioral tests were recorded by the same investigator, who was blinded to the animal grouping as previously described [9,20]. Those animals were not subjected to further laboratory analysis.…”
Section: Behavioral and Cognitive Testsmentioning
confidence: 99%
“…The FCT was performed as described by Zhang et al [20,21] with modifications. The training in FCT (XR-XC404, Shanghai Xin Soft Information Technology Co. Ltd.) was performed as follows.…”
Section: Fear Conditioning Test (Fct)mentioning
confidence: 99%